A Novel Nutrient Mixture Induces Apoptosis in Human Mesothelioma Cells (MSTO-211H) via Activation of Caspases - M Waheed Roomi; Bilwa Bhanap; Aleksandra Niedzwiecki; Matthias Rath (Global Journal of Cancer Therapy - Peertechz Publications, 2019)
Background: Malignant mesothelioma is a highly aggressive and fatal cancer of older people. Consistently associated with asbestos exposure, mesothelioma is diagnosed when it is extensively metastasized and it has a dismal prognosis.  Purpose of the study: Surgery, chemotherapy, and radiotherapy are the mainstay of treatment yet they are ineffective in increasing the mesothelioma patient survival. Therefore, a different approach is needed. A novel nutrient mixture containing green tea extract, ascorbic acid, lysine, and proline exhibited anti-cancer effects in various cancers. In our previous studies, the nutrient mixture was seen to block MMP secretion and invasion through MatrigelTM by mesothelioma cells. In the current study, we wanted to explore if the nutrient mixture could induce apoptosis in mesothelioma cells.  Results and main findings: The mesothelioma MSTO-211H cells were cultured in complete Ham F-12K medium and the cells were then treated with the nutrient mixture at 0-1000 µg/ml concentration. Cell cytotoxicity was measured by MTT assay, morphology by H&E staining, and the apoptosis by LIVE Green Caspases. The nutrient mixture did not show significant inhibition of cell proliferation. However, H&E staining at the dose of 100 µg/ml showed a few cellular changes, while significant changes pertaining to apoptosis morphology were observed at 500 and 1000 µg/ml. LIVE Green Caspases analysis showed cells in early an d late apoptosis with increasing doses of the nutrient mixture.  Conclusions: Our results suggest that the nutrient mixture may provide a new supplemental strategy for enhancing the therapeutic options for mesothelioma